Historical representations and conflicts about indigenous people as national identities - Carretero, Mario (2011)
The relation between history learning processes, in and out of school, and the construction of national identities is nowadays an increasingly important topic, being studied through the appropriation of historical narratives, which are frequently based on the official history of any nation state. In this paper, college students' historical representations of their nation's origin are studied. We compared specific quantitative answers about who the first inhabitants of Argentina were with more in depth qualitative answers about their nation's political origin. In this respect, a conflict has been found in the way students present the official narrative. This conflict consists of maintaining that natives were the first national inhabitants, while most of the students think their nation was created in the 19th century. Different reactions to this are analyzed, particularly students' efforts to justify this conflict and to find coherency in historical content which has been produced by school history teaching and other sources and consumed by college students. The most common justifications include cultural tools that conceal the violence historically suffered by the natives, and at the same time an unreal conciliation between natives' rights and the interests of western founders of the national state. These tensions are considered in light of sociocultural discussions about the differences between production and consumption of historical narratives and their appropriation. We uphold that consumed historical narratives are based on an ontological and ahistorical concept of one's own nation, which prevents understanding a possible counternarrative based on natives as historical agents.